2009
DOI: 10.2500/ajra.2009.23.3308
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Airflow in the Nasal Cavities: Implications for Nasal Air Conditioning and Epistaxis

Abstract: The airflow simulations indicate that the inferior and middle turbinates and Little's area on the anterior nasal septum contribute significantly to nasal air-conditioning. The concentration of wall shear stress within Little's area indicates a desiccating and potentially traumatic effect of inhaled air that may explain the predilection for spontaneous epistaxis at this site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…Previous investigation by Bailie et al 19 demonstrated that increased elevated WSS had a negative effect on nasal air conditioning, with inhaled airflow that leads to mucosal desiccation and local trauma. This was performed by using CFD models in asymptomatic adults without prior nasal surgery, but currently there are no available data that characterize the wall-shear changes in the postsurgical maxillary sinus and its clinical implications.…”
Section: Figure 4 Average Values On the Diseased And Nondiseased Sidmentioning
confidence: 98%
“…Previous investigation by Bailie et al 19 demonstrated that increased elevated WSS had a negative effect on nasal air conditioning, with inhaled airflow that leads to mucosal desiccation and local trauma. This was performed by using CFD models in asymptomatic adults without prior nasal surgery, but currently there are no available data that characterize the wall-shear changes in the postsurgical maxillary sinus and its clinical implications.…”
Section: Figure 4 Average Values On the Diseased And Nondiseased Sidmentioning
confidence: 98%
“…The mucosa was easy to dry and cause bleeding under mucosa due to angiorrhexis, the conclusion of which was consistent with the common clinical bleeding of the front end of the nasal cavity localized in general at the Bthe little region[ of the rear region of nasal valve. 6 When air flowed through the local narrow region and had relatively more differences of up-and-down flow rates as air flowed through the axial direction, it was easy to cause vortex. The nasal cavity of the patient with Crouzon syndrome produced stream swirl easier compared with the normal nasal cavity.…”
Section: Discussionmentioning
confidence: 98%
“…It was a very mature technique for CFD to be used for the analysis and research on the airflow field of the nasal cavity. Bailie et al, 6 Ishikawa et al, 3 9 have also applied CFD to study the airflow field features of the pathologic structure of the nasal cavity and investigate the effect of the changed postoperative structure of the nasal cavity on its flow field in hypertrophy of nasal turbinates and atrophic rhinitis. From the angle of fluid dynamics, analyzing the pathologic and physiologic bases of the cause could provide reference to an operative layout and objective.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the cases, no specific cause is found. In a majority of them, the bleeding is at the little's area from Keisselbach's plexus [5] [Table/ Fig-3]. The bleeding is minimal and it is not life threatening.…”
Section: Discussionmentioning
confidence: 99%